Beetroot Peel Extract as a Natural Preservative for Shelf life Extension of Deccan mahseer (Tor khudree) Steaks during Chill Storage - Maqbool, Hafsa; Safeena, M. P.; Sathish Kumar, K.; Zynudheen, A. A.; Ninan, George; Manoj Kumar, B. (Fishery Technology, 2019)
The efficacy of solvent free beetroot (Beta vulgaris) peel extract in retarding the lipid oxidation of mahseer steaks were evaluated during chill storage. Preliminary analysis of the beetroot peel extract (BPE) for antioxidant activity were evaluated based on the total phenolic content, 2, 2-diphenyl-1- picrylhydrazyl radical scavenging activity and 2, 2- azino-bis (3-thylbenzothiazoline-6-sulfonic acid radical scavenging activity. BPE had total phenolic content of 360.47 mg 100 g-1; both DPPH activity (91.62%) and ABTS radical scavenging activity (99.04%) were found to be higher at 20% concentration. Mahseer steaks were given dip treatment in beetroot peel extract (20%, w/v) then packed in LDPE pouches and kept at 0-2Â°C. The effect of dip treatment on quality changes of steaks were assessed periodically for biochemical (pH, PV, FFA, TBA, TMA, TVB-N), microbiological (total plate count) and sensory characteristics along with control sample. The microbial analysis revealed that the control (CT) sample reached to the limit of acceptability (7.47 log cfu g-1) on 9th day while treated sample remained within the limit up to 15th day of storage. Sensory evaluation also showed the decreasing trend as the storage days increased. The results showed that CT sample exceed the acceptable limits on 9th day of storage, whereas the BPE treated sample was found to be acceptable up to 15th day indicating the positive role of BPE in shelf life extension of masher steaks under chilled storage (0-2Â°C).